eIF5A is activated by virus infection or dsRNA and facilitates virus replication through modulation of interferon production - Seoane, Rocío; Llamas-González, Yessica Y.; Vidal, Santiago; El Motiam, Ahmed; Bouzaher, Yanis Hichem; Fonseca, Danae; Farrás, Rosa; García-Sastre, Adolfo; González-Santamaría, José; Rivas, Carmen (Frontiers in Cellular and Infection Microbiology, 2022)
Active hypusine-modified initiation elongation factor 5A is critical for cell proliferation and differentiation, embryonic development, and innate immune response of macrophages to bacterial infection. Here, we demonstrate that both virus infection and double-stranded RNA viral mimic stimulation induce the hypusination of eIF5A. Furthermore, we show that activation of eIF5A is essential for the replication of several RNA viruses including influenza A virus, vesicular stomatitis virus, chikungunya virus, mayaro virus, una virus, zika virus, and punta toro virus. Finally, our data reveal that inhibition of eIF5A hypusination using the spermidine analog GC7 or siRNA-mediated downmodulation of eIF5A1 induce upregulation of endoplasmic reticulum stress marker proteins and trigger the transcriptional induction of interferon and interferon-stimulated genes, mechanisms that may explain the broad-spectrum antiviral activity of eIF5A inhibition.